Integrate, Attend and Prevent: An Itinerary at the Service of Recovery and Reparation for victims of sexual abuse within the Catholic Church - Compte Grau, M.ª Teresa (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
This article discusses the difficulties facing the Catholic Church in developing and implementing comprehensive care procedures aimed at the recovery and restitution of victims of sexual abuse within the Church. To accomplish this task, the Church must provid itself with scientific knowledge that enables it to understand the factors that contribute to and perpetuate abuse, the mechanisms that promote silence and result in secondary victimization. Victimology, as a social science focused on the study of victimization and de-victimization processes, offers key concepts that, in dialogue with Theology, Canon Law, and Social Doctrine, may provide the Catholic Church with the necessary knowledge and vocabulary suitable for this task.
Keywords: sexual abuse; abuse of power; victimization; secondary victimization; victim recovery; reparation; restoration; religious trauma; betrayal of trust; memory